A critical realist explanation for the capabilities of people with disabilities in dealing with disasters. Issue 3 (4th May 2023) - Ton, Khanh That; Gaillard, J. C.; Adamson, Carole; Akgungor, Caglar; Ho, Ha Thanh
ABSTRACT: The capability approach has recently been recognised as a potential explanatory theory in disability research. However, to strengthen its explanatory power, it is argued that it should be grounded in a critical realist research paradigm. While critical realism is increasingly adopted in social inquiry, to date there remains little research that elaborates how a critical realist methodology is applied in capability and disability research, especially in the context of disasters. To bridge this gap, this study provides an empirical example of how a critical realist methodology can be used to explain the capabilities of people with disabilities to deal with disasters.